One-dimensional modelling of the thinning of particulate suspensions near pinch-off. (November 2018) - Rubio-Rubio, Mariano; Mathues, Wouter; Sevilla, Alejandro; Clasen, Christian
Highlights: Near pinch-off dynamics of a colloidal suspension responds to Newtonian behaviour with an additional active stretching due to end particles movement. Modelling of the interstitial fluid as an axially stretching Newtonian liquid bridge with a non-uniform movement of the boundaries. One-dimensional model in excellent agreement with experimental results for different particle sizes, concentrations and suspending medium viscosities. Abstract: This paper deals with the thinning dynamics of a liquid bridge of dilute particulate suspensions in a Newtonian matrix. We describe the final stage before break-up of a colloidal suspension, which occurs in a liquid thread between two confining beads. The model, based on the one-dimensional mass and momentum conservation equations, shows quantitative agreement with the experimentally observed deceleration and final pinching behaviour of the medium between individually monitored particles in the suspension (Mathues et al., 2015) and thus supports the hypothesis that an accelerated thinning of the Newtonian matrix is caused by an active stretching via independently moving particles.